Establishing BioE3 centres: catalyzing India’s biomanufacturing transformation - Kumar, Dhiraj; Kumar, Jitendra (Frontiers in Bioengineering and Biotechnology, 2025)
India’s bioeconomy is poised for rapid expansion, targeting a valuation of $300 billion by 2030. The recently approved BioE3 Policy (Biotechnology for Economy, Environment, and Employment) aims to reposition India as a global leader in sustainable, high-performance biomanufacturing. In this context. a national stakeholder meeting was convened with ∼75 participants, including CEOs, COOs, and senior representatives from bioincubators, Centres of Excellence, startups, and scientific institutions. Structured group discussions and expert inputs focused on operationalizing BioE3 Centres—new-generation incubation and biomanufacturing hubs aimed at bridging critical infrastructure and capability gaps]. Discussions identified the need for pilot-scale infrastructure, regulatory-grade facilities, skilled human resources, and integration with existing policy mechanisms such as the Biotechnology Industry Partnership Programme (BIPP) and the Entrepreneur-in-Residence (EIR) initiative under BIRAC. Once fully operational, BioE3 Centres are projected to support over 250 startups and MSMEs, generate an estimated 10,000 skilled jobs, and contribute up to $25 billion to India’s targeted $300 billion bioeconomy by 2030. This article outlines the key insights, recommendations, and phased implementation roadmap from the consultation, with implications for national policy execution and global positioning of India’s bioeconomy.